Vision of physical education teachers in secondary education in Andalusia on outdoor activities - Francisco Javier Giménez Fuentes-Guerra; José María Rodríguez López; Jesús Sáez Padilla (FEADEF, 2011)
The opinions and participation of physical education teacher who teaches in the Secondary Education in the andalusian community has allowed us to investigate a block content of the curriculum of the subject. We have been watching since the beginning of our work, the activities in the environment as a block of content on the subject of interest to teacher of physical education, however, curriculum development in schools in poor andalusians. From the methodological rigor, has conducted a comprehensive analysis of legislation, relevant documents and information that form the theoretical framework of research. The following has been collected through questionnaires and interviews, the views of physical education teachers and input from experts trainers in activities in the environment. After analysis and discussion of the results have raised some improvements with the future outlook related to training, physical education teacher in the Secondary Education in Andalucia and activities in the environment. For example, the incorporation of progressive form of classical training and education activities of non-formal education such as: camping and camps